Finite Math and Applied Calculus (6th Edition)

Published by Brooks Cole
ISBN 10: 1133607705
ISBN 13: 978-1-13360-770-0

Chapter 0 - Section 0.5 - Solving Polynomial Equations - Exercises - Page 30: 19



Work Step by Step

$-x^{2}-2x-1=0$ $x=\frac{2\pm \sqrt (2^{2}-4(-1)(-1))}{-2}=\frac{2\pm \sqrt 0}{-2}=\frac{2}{-2}=-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.